Interactions between the female parasitoid Epidinocarsis lopezi De Santis (Hym., Encyrtidae) and its host, the cassava mealybug, Phenacoccus manihoti Matile-Ferrero (Hom., Pseudococcidae) - Löhr, Bernhard; Neuenschwander, Peter; Varela, Ana M.; Santos, B. (Wiley, 1988)
In laboratory experiments, the influence of different host instars and population densities of the cassava mealybug (CM), Phenacoccus manihoti Matile‐Ferrero, on the reproductive performance of the encyrtid parasitoid Epidinocarsis lopezi (De Santis), was investigated. In choice experiments, fourth instar hosts were examined most frequently, but third instar hosts were stung most often. Stinging was followed by oviposition in 87.7% of all third instar CM, and 57.1% of all second instars. At constant temperatures, no daily rhythmicity in egg laying could be detected. When different host densities were offered in a no‐choice experiment, parasitization at the lowest density was only one mummy per day, i.e. less important than host feeding. It then increased to 10 mummies per day when 30 or more CM were offered. Mortality from host feeding also increased with increasing host densities, but much less than the one by mummy formation. It was most important on second instars where it accounted for 48.2% of the total mortality inflicted by the parasitoid and decreased to 4.1% in the last instar. Starved females (for 36 h) consumed slightly more CM than well fed ones, but only when held at 30 °C. Some stung CM (12.0% in the third instar) showed retarded growth and impaired reproduction. In those which contained a parasitoid larva (one third for the third instar), E. lopezi failed to finish the development. The mortality caused by successful reproduction of E. lopezi , host feeding, mutilation, and arrestment of host development is summarized for the different CM instars. The high adaptability of E. lopezi is discussed.